AI ethics - Coeckelbergh, Mark, (Cambridge, MA : The MIT Press, 2020)
"AI ethics is much debated today and often attracts fears about superintelligence. This book, written by a philosopher of technology engaged in research and policy on the topic, moves away from science fiction fantasies and instead focuses on concrete ethical issues raised by AI and data science. After contextualizing nightmares about AI and sketching some philosophical issues, it looks at what the technology actually is and discusses problems such as responsibility, transparency, and bias. It also gives an overview of AI policy and discusses its challenges - also in the light of climate change. The book ends with a call for more wisdom next to intelligence"-- "AI ethics is much debated today and often attracts fears about superintelligence. This book, written by a philosopher of technology engaged in research and policy on the topic, moves away from science fiction fantasies and instead focuses on concrete ethical issues raised by AI and data science. After contextualizing nightmares about AI and sketching some philosophical issues, it looks at what the technology actually is and discusses problems such as responsibility, transparency, and bias. It also gives an overview of AI policy and discusses its challenges - also in the light of climate change. The book ends with a call for more wisdom next to intelligence"--